Uso de marcadores moleculares para determinar a variabilidade genética no papa (solanum tuberosum) - Yzarra Aguilar, Adelfa (2020)
The objective was to understand the use and importance of genetic markers used in studies of genetic diversity in potatoes. The most relevant publications of the last twenty years were reviewed in SciELO, LILACS and PUBMED databases scrutinizing the technique used, the main results obtained from the use and evolution of the main marking methodologies in recent years and a better understanding of the techniques most commonly used, concluding that potato cultivars discriminate more accurately with DNA-based markers, since protein-based markers do not discriminate in their entirety.